HIV status and the risk of ischemic stroke among men. - Sico, Jason J; Chang, Chung-Chou H; So-Armah, Kaku; Justice, Amy C; Hylek, Elaine; Skanderson, Melissa; McGinnis, Kathleen; Kuller, Lewis H; Kraemer, Kevin L; Rimland, David; Goetz, Matthew Bidwell; Butt, Adeel A; et al. (Neurology, 2015)
Given conflicting data regarding the association of HIV infection and ischemic stroke risk, we sought to determine whether HIV infection conferred an increased ischemic stroke risk among male veterans.
Keywords: Brain Ischemia; Causality; Cohort Studies; Comorbidity; HIV Infections; Humans; Incidence; Male; Men's Health; Middle Aged; Risk Factors; Stroke; United States; Veterans